Community pharmacists’ engagement with Raqeeb platform: perceptions and implementation challenges toward controlled substance monitoring in Saudi Arabia - Alshahrani, Sultan M. (Frontiers in Pharmacology, 2025)
IntroductionThe misuse of narcotic drugs and psychotropic substances (NDPS), especially gabapentinoids, poses a considerable public health concern in Saudi Arabia, leading to the establishment of the Raqeeb platform, a nationwide electronic platform for the real-time monitoring of NDPS prescriptions. This study aimed to assess community pharmacists’ perceptions, engagement, and implementation challenges with the Raqeeb platform in order to inform future improvements.MethodsA cross-sectional descriptive study was performed from March to May 2025, targeting licensed community pharmacists in Saudi Arabia. A standardized, self-administered questionnaire, validated by experts and piloted with 15 pharmacists, evaluated knowledge, attitudes, and operational challenges using a five-point Likert scale. Convenience sampling through professional networks and social media produced 270 responses. Data were analyzed with IBM SPSS Statistics version 26, employing descriptive statistics and Cronbach’s alpha to assess reliability.ResultsParticipants (58.1% male, 62.2% PharmD, 78.1% with less than 5 years of experience) demonstrated strong awareness of Raqeeb’s objectives and its role in enhancing safety. Most respondents supported mandatory training and nationwide expansion of the platform. However, challenges were reported, including limited integration with pharmacy systems, complexity of the interface, and unavailability of certain controlled drugs. Cronbach’s alpha values (0.73–0.87) confirmed the instrument’s reliability.ConclusionCommunity pharmacists recognize the public health value of Raqeeb; however, its best use has been limited by issues with usability, integration, and training. Addressing these barriers through system integration, structured training, and improved medication availability is essential to strengthening NDPS monitoring and advancing Vision 2030 digital health goals.